2015
DOI: 10.1126/scitranslmed.aaa9853
|View full text |Cite
|
Sign up to set email alerts
|

Results of a preclinical randomized controlled multicenter trial (pRCT): Anti-CD49d treatment for acute brain ischemia

Abstract: A multicenter preclinical, randomized, controlled trial (pRCT) of a potential stroke treatment in mice demonstrates the feasibility of performing clinical trial–like investigations in animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
212
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(218 citation statements)
references
References 57 publications
3
212
0
3
Order By: Relevance
“…Previous trials of immunomodulatory therapies have focused on attenuating the detrimental effects of certain immune cells and inflammatory mediators on the extent of tissue damage in the acute phase. Despite solid evidence, including metaanalyses [44], and preclinical randomized trials for the effectiveness of this neuroprotective approach in experimental studies, the translational validity of neuroprotection by immune modulation is presently uncertain [70]. Findings in proof-of-concept neuroimaging studies in T lymphocytes are controversial and require further investigation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Previous trials of immunomodulatory therapies have focused on attenuating the detrimental effects of certain immune cells and inflammatory mediators on the extent of tissue damage in the acute phase. Despite solid evidence, including metaanalyses [44], and preclinical randomized trials for the effectiveness of this neuroprotective approach in experimental studies, the translational validity of neuroprotection by immune modulation is presently uncertain [70]. Findings in proof-of-concept neuroimaging studies in T lymphocytes are controversial and require further investigation.…”
Section: Future Directionsmentioning
confidence: 99%
“…For instance, fingolimod, a drug that induces lymphopenia and prevents lymphocyte access to the brain, has shown beneficial effects in stroke animal models [145] and in small clinical trials in ischemic patients with stroke [146,147]. Also, natalizumab, a drug that inhibits leukocyte infiltration, seems to exert some benefits in human stroke (ACTION trial), and a corresponding mouse anti-CD49d antibody has shown protective effects but only in 1 of 2 experimental models of brain ischemia [148]. Larger studies in patients with stroke are needed to demonstrate efficacy and safety of immunodulatory strategies.…”
Section: Sai and Brain Damagementioning
confidence: 99%
“…Therapeutic hypothermia Reduce oxygen demand, disruption of the blood-brain barrier, free radical formation, excitotoxicity, and inflammation Intravascular cooling (ICTuS2 trial) [38] or surface cooling [47] in IVT-treated patients was safe despite the adverse events (e.g., pneumonia), but did not improve outcome. A multicenter phase III RCT (EuroHYP-1, NCT01833312) is ongoing to evaluate the effect of surface/endovascular cooling after IVT or EVT.…”
Section: Magnesiummentioning
confidence: 99%